ANALISIS PERTANGGUNGJAWABAN TERHADAP HUKUM COVERNOTE NOTARIS (STUDI PUTUSAN MAHKAMAH AGUNG NO. 181/PDT/2019/PT.MKS) - Apresya Handayani Sembiring (Jurnal Perspektif Hukum, 2022)
The covernote is not an authentic deed because it does not meet the requirements of the deed as stated in Article 1868 of the Civil Code. In general, a covernote is a letter explaining that there is an ongoing process in the management of unfinished deeds. In the case of a Notary issuing a covernote on the basis of a Notary being asked to manage, complete and carry out a legal relationship between the parties as a form of responsibility to serve the community. The research method used in this research is the Juridical Empirical method which is descriptive analytical, data collection is carried out using secondary data in the form of primary materials. The results of the study show that the act of a Notary issuing a Covernote can potentially become an unlawful act if the elements of an unlawful act are fulfilled. The act of issuing a Covernote which is potentially against the law, apart from being seen from the point of view of propriety, can also be seen from the error of the Notary concerned. Notaries who commit acts that are against the law will be sanctioned. Notary is part of the awareness that the Notary in carrying out his duties and position has violated the provisions regarding the implementation of the Notary's duties. The imposition of sanctions on Notaries is also to protect the public from Notary actions that can harm the community. This is related to the Supreme Court Decision Number 181/PDT/2019/PT MKS regarding the Notary's Accountability to the Covernote he made. Where the Covernote that is published itself is not carried out in accordance with the contents of the covernote, the Notary will be given a Civil Sanction.